Mediacja jako instrument polityki władz gminy służący zapewnieniu realizacji zasady zrównoważonego rozwoju w planowaniu przestrzennym - Federczyk, Wojciech (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Settlements taken in the process of local spatial planning are very important for the implementation of the principle of sustainable development. It is therefore important to ensure public participation in them. The article contains an analysis of the legal forms of public participation in spatial planning and identifies the benefits of using mediation. Involvement the parties in negotiations with the presence of the mediator could bring benefits to both: municipal authorities and parties. It makes easier reaching an optimal planning solution by the authorities and the parties receive opportunity to realize their plans and interests. Mediation as a form of multilateral communication can better meet the requirements of participatory democracy than those provided by the law of public consultation which have forms of notes or participation in public discussion.
Keywords: mediacja; partycypacja społeczna; zrównoważony rozwój; lokalne planowanie przestrzenne